2(9x-7)+2(2x-6)=

Simple and best practice solution for 2(9x-7)+2(2x-6)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(9x-7)+2(2x-6)= equation:


Simplifying
2(9x + -7) + 2(2x + -6) = 0

Reorder the terms:
2(-7 + 9x) + 2(2x + -6) = 0
(-7 * 2 + 9x * 2) + 2(2x + -6) = 0
(-14 + 18x) + 2(2x + -6) = 0

Reorder the terms:
-14 + 18x + 2(-6 + 2x) = 0
-14 + 18x + (-6 * 2 + 2x * 2) = 0
-14 + 18x + (-12 + 4x) = 0

Reorder the terms:
-14 + -12 + 18x + 4x = 0

Combine like terms: -14 + -12 = -26
-26 + 18x + 4x = 0

Combine like terms: 18x + 4x = 22x
-26 + 22x = 0

Solving
-26 + 22x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '26' to each side of the equation.
-26 + 26 + 22x = 0 + 26

Combine like terms: -26 + 26 = 0
0 + 22x = 0 + 26
22x = 0 + 26

Combine like terms: 0 + 26 = 26
22x = 26

Divide each side by '22'.
x = 1.181818182

Simplifying
x = 1.181818182

See similar equations:

| 2x^2+3x^2=84 | | 7(D-5)=12+5 | | -4(5x-5)+11x=3(-7x-9)-49 | | 12*sinx=6 | | 14x-8x=27 | | 6x-x-15= | | 5k-3(k-2)=-24 | | 5x^3-5x^2+12x=0 | | -4n-12=2+5n+4 | | 5m+5=10 | | 12cosx=6 | | 0=5r+6r | | Cx+8x-3y+7=0 | | .50r+5=1r | | 5y-1y=3 | | 2/5c+4-1.5c=-9 | | 7(n+5)-6=4(1+8n) | | 5-6n=5-6n | | 7b-5-5b=15-2b | | 4-5x=22 | | 0.45=logx | | 7+25x=38+18x | | -6-3y=2 | | 125m+75m+48000=50000-200m | | -n=-8+2n | | 7d+2=9d-5 | | 4-5=22 | | 9+6+4x+9=x | | 30+2x=40+1x | | 2x+9-9x=13-15x+8x-4 | | 1x-7=-1 | | 3(2d+7)=29 |

Equations solver categories